OPTIMIZATION OF INVARIANT TRAINING OF TEACHERS OF HIGHER EDUCATION INSTITUTION ON THE BASIS OF SYNERGETIC EFFECT HOLISTICHNY INFORMATION AND EDUCATION ENVIRONMENT - Alla L. Busygina; Vladimir N. Aniskin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
From positions of logiko-associative and synonymous and semantic approaches key concepts of the thesaurus of research of invariant training of teachers of higher education institution are concretized. Feature of a present noosphere stage of development of system of higher education, the events in the conditions of new information space and the competence-based focused education paradigm is detailed. Relevance of a problem of integration locates in didactics of the higher school which is considered from a position of the formalizing, substantial defining, administrative and holistichno-technological approaches. Models of the information and education environment of higher education institution and the holistichny environment of educational institution are compared and on the basis of this projection concepts of the holistichny information and education environment of higher education institution and synergetic effect which it has definirutsya. The features of the holistichny environment of higher education institution allowing to make the assumption of its compliance to the basic synergetic principles of education adapted for process of optimization of invariant training of teachers of higher education institution in this environment and providing polyfunctionality of preparation are considered. The analysis of the maintenance of the main professional educational programs of the higher education, level of preparation of the research and educational personnel in postgraduate study, the Education directions and pedagogical sciences is carried out. Results of this analysis show that irrespective of a profile of programs of preparation for obligatory types of professional activity of graduates of postgraduate study belong research and teaching activity in educational and social spheres. And the generalized labor functions of graduates of postgraduate study include along with independent research activities and specialized functionality for a concrete profile, scientific and pedagogical work in the highest and average professional educational organizations of various forms of ownership. Additional possibility of optimization of invariant training of teachers of higher education institution due to synergetic effect of the holistichny information and education environment is proved.